Christian neo-orthodoxy approach to reconstruction of religious thought on selected theological issues: an lslamic analysis - Abdul Rahim, Adibah (2018)
Christian neo-orthodoxy can be placed as a middle position between traditional orthodoxy and liberalism. Like Muslim reformists’ approach of reform, which attempted to reconstruct Islamic religious thought in the light of modern science and knowledge, Christian neo-orthodoxy insisted that Christianity itself needs continually to be rethought and that theology must engage seriously with the modern world in its quest for understanding. Therefore, both Islamic approach of reform and Christian neo-orthodoxy shared a similar objective, but both present different views and methods of interpreting scriptures and traditions in the light of new scientific knowledge. This paper highlights selected theological issues advocated by Christian neo-orthodoxy for reconstruction of religious thought. At the same time, it provides an analysis on those issues from Islamic perspectives. It was found that despite of claiming themselves as belong to mediating position, Christian neo-orthodoxy seemed to ignore their scriptures and depended much on human interpretations. This is obviously contradicted to an Islamic approach which upholds that the fundamental sources of the Qur’an and Sunnah should always be referred to as primary references despite our reliance on modern knowledge and rational inquiries. Since the study is theoretical in nature, it is confined to library research. It is hoped that this study will provide a proper understanding on the response of religious thought from the perspective of two different religions, Christianity and Islam.